Zakat dan Pajak Dalam Pemikiran Yusuf Qardhawi dan Masdar Farid Mas’udi - Sudarmaji, Waluyo (MADINAH, 2019)
The study discusses the opinions of Yusuf Qardhawi and Masdar Farid Mas’udi about alms and tax. Where the researcher feels there is an interest to explore more deeply from this two opinions, the both have the uniqueness thought wich very clearly visible accros the ijtihad about the wage of alms and tax. Yusuf Qardhawi argue that alms and tax very different and payment method cannot put together. While Masdar Farid Mas’udi argue about alms and tax altought between alms and tought different but cannot separated and payment method can put together. As the main points is to examine the istinbāth law of Yusuf Qardhawi and Masdar Farid Mas’udi then to know the stronger arguments is used by Yusuf Qardhawi and Masdar Farid Mas’udi about alms and tax. This research is library research by Fiqh az-Zakat book and Pajak itu Zakat book accompanied by interview with character directly via whatsapps. The result research with all the author capabilities, maximally to try analyze from two opinion Yusuf Qardhawi’s opinion above is amore superior than Masdar Farid Mas’udi’s opinion. It can be accepted because his opinion is in harmony of common of cleric.